Fgfr3 Is a Positive Regulator of Osteoblast Expansion and Differentiation During Zebrafish Skull Vault Development. (26th May 2020) - Dambroise, Emilie; Ktorza, Ivan; Brombin, Alessandro; Abdessalem, Ghaith; Edouard, Joanne; Luka, Marine; Fiedler, Imke; Binder, Olivia; Pelle, Olivier; Patton, E Elizabeth; Busse, Björn; Menager, Mickaël; et al.
ABSTRACT: Gain or loss‐of‐function mutations in fibroblast growth factor receptor 3 (FGFR3) result in cranial vault defects highlighting the protein's role in membranous ossification. Zebrafish express high levels of fgfr3 during skull development; in order to study FGFR3's role in cranial vault development, we generated the first fgfr3 loss‐of‐function zebrafish (fgfr3 lof/lof ). The mutant fish exhibited major changes in the craniofacial skeleton, with a lack of sutures, abnormal frontal and parietal bones, and the presence of ectopic bones. Integrated analyses (in vivo imaging and single‐cell RNA sequencing of the osteoblast lineage) of zebrafish fgfr3 lof/lof revealed a delay in osteoblast expansion and differentiation, together with changes in the extracellular matrix. These findings demonstrate that fgfr3 is a positive regulator of osteogenesis. We conclude that changes in the extracellular matrix within growing bone might impair cell–cell communication, mineralization, and new osteoblast recruitment. © 2020 American Society for Bone and Mineral Research.